Incorporation of p-53 mutation status and Ki-67 proliferating index in classifying Her2-neu positive gastric adenocarcinoma. Issue 1 (1st January 2018) - Ahmed, Ayesha; Al-Tamimi, Dalal M.
ABSTRACT: Her2-neu overexpression has a pathogenetic, therapeutic and a controversial prognostic role in gastric cancer. p-53 mutation status and Ki-67 proliferation index are established prognostic markers in many tumors. In this study we evaluated p-53 and Ki-67 in relation to Her2-neu positive and negative gastric adenocarcinoma (GA). This cross-sectional study was carried out at King Fahd Hospital of Imam Abdulrahman bin Faisal University. Fifty cases of GA were retrieved from pathology archives. Clinico-pathological parameters were evaluated. Immunohistochemical protein analysis for Her2-neu, Ki-67 and p-53 was carried out. Fluorescent in situ hybridization (FISH) analysis was done for Her2-neu positive cases showing 2+ immunoexpression. Frequency of Ki-67 and p-53 positivity in Her2-neu positive cases was calculated and compared with those in Her2-neu negative cases. Correlation of clinicopatological parameters with Her2 positive and negative cases, p -53 mutation status and Ki-67 proliferation index was carried out. Her2-neu overexpression was present in 12% ( n  = 6) cases. A high Ki-67 was seen predominantly in Her2-neu positive cases (83%, n  = 5). Her2-neu negative cases ( n  = 44) showed moderate (31.88%, n  = 14) to low (34%, n  = 15) Ki-67. Diffuse p-53 positivity was seen predominantly in Her2-neu positive cases (33.33%, n  = 2). Focal p-53 was seen mainly in Her2-neu negative cases 56.8% ( n  = 25). Negative p-53 was seen to be independent of Her2-neu status. Her2-neu positivity is strongly associated with diffuse p-53 mutation status and high Ki-67 proliferation. Her 2-neu negative status is associated with focal p-53 positivity and low to moderate Ki-67 proliferation index. Such stratifications in prognostic markers could not only be predictive in patient's prognostics but could also form a basis of molecular classification of gastric cancer.